Political Economy of Power Sector Subsidies : A Review with Reference to Sub-Saharan Africa - Kojima, Masami (World Bank Group, Washington, DC, 2014)
Power sector subsidies in Sub-Saharan Africa are substantial and highly regressive. While subsidies can be quick, easy, and politically expedient to implement, they are equally quick to take root and challenging to remove. Optimal policies that are technically sound and welfare-enhancing over the long run have nevertheless been found difficult to launch and even more challenging to sustain. Of the barriers to reform, those associated with political economy are among the most powerful, yet their analysis is often lacking due consideration in the reform design process. This paper reviews the literature on power subsidies and their reform with emphasis on the political economy of such reform. It examines pricing principles in the power sector and different types of subsides; drivers for subsidies, benefits and costs of subsidy reform, and their distribution; and approaches to political economy analysis, tools available, and methodological issues. The paper draws examples from Sub-Saharan Africa and elsewhere, and presents case studies from the literature.